NMDA and not non-NMDA receptor antagonists are protective against seizures induced by homocysteine in neonatal rats - Folbergrová, J (Experimental neurology, 1994)
Homocysteine induces seizures in adult, as well as in immature, experimental animals, but the mechanism of its action is still unknown. The aim of the present study was to examine whether homocysteine in immature animals may act via excitatory amino acids receptors. Seizures were induced in 7-day-old rats by ip administration of homocysteine (16.5 mmol/kg) and the effects of selected antagonists at NMDA and non-NMDA receptor sites were investigated. The anticonvulsant effect was evaluated not only in terms of behavioral changes, but also in terms of some indicators of brain energy metabolism. Rat pups were sacrificed during generalized clonic-tonic seizures, corresponding approximately to 15-30 min after homocysteine administration. Comparable time intervals were used for sacrificing pups in the groups with protective drugs. Non-NMDA antagonists, L-glutamic acid diethylester (GDEE) (4 mmol/kg, ip) and 2,3-dihydroxy-6-nitro-7-sulfamoyl-benzo (F) quinoxaline (NBQX) (two doses, 30 mg/kg each, ip), failed to protect neonatal rats against homocysteine-induced seizures. Although NBQX prevented the tonic phase, the severity of clonic movements was even more pronounced. Metabolic changes accompanying the seizures (decreases of glucose and glycogen and a rise of lactate) were also not influenced by GDEE or NBQX pretreatment. On the contrary, NMDA antagonists, both competitive (AP7, 0.33 mmol/kg, ip) and noncompetitive (MK-801, 0.5 mg/kg, ip), had a clear-cut anticonvulsant effect. They not only suppressed the behavioral signs of seizures, but also prevented most of the metabolic changes accompanying seizures.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: receptory N-methyl-D-aspartátu; 2-amino-5-fosfonovalerát; záchvaty; Rats; Animals, Newborn; neuroprotektivní látky; 2-Amino-5-phosphonovalerate; Male; Neuroprotective Agents; receptory aminokyselin; homocystein; antikonvulziva; dizocilpinmaleát; mužské pohlaví; chinoxaliny; Rats, Wistar; Receptors, N-Methyl-D-Aspartate; Seizures; novorozená zvířata; Homocysteine; glutamáty; Glutamates; krysa rodu Rattus; Quinoxalines; zvířata; Anticonvulsants; Dizocilpine Maleate; Receptors, Amino Acid; potkani Wistar; AMPA receptory; aminokyseliny; Receptors, AMPA; Amino Acids; Animals